Cosensitization of metal-based dyes for high-performance dye-sensitized photovoltaics under ambient lighting conditions. (October 2021) - Saeed, Muhammad Ahsan; Kang, Hyeong Cheol; Yoo, Kicheon; Asiam, Francis Kwaku; Lee, Jae-Joon; Shim, Jae Won
Abstract: With the emergence of Internet of Things, dye-sensitized photovoltaics (DSPVs) have attracted considerable interest for indoor energy harvesting over the past decade. In this study, a cosensitization approach is applied by mixing ruthenium-based dyes to achieve an increased DSPV performance under low-intensity light conditions. The optimized cosensitized DSPV exhibits an excellent power-conversion efficiency of about 20.7% under a 500-lx light-emitting diode illumination, superior to those of single N719 (16.1%) and N749 (14.8%) under the same illumination conditions. The improved performance of the cosensitized device can be attributed to the panchromatic absorption of the mixed dyes. In addition, an electrochemical impedance analysis is performed to analyze the charge transfer kinetics of the single and cosensitized devices at the TiO2 /dye/electrolyte interface. The exceptional indoor performance of the cosensitized DSPV can be attributed to the increased external quantum efficiency, sharp increase in the current density with an increased broadening of the absorption window, and balanced charge transport characteristics. The findings of this study suggest that cosensitization is a useful technique for the realization of high indoor performances of DSPVs. Graphical abstract: Image 1 Highlights: Cosensitization with ruthenium-based dyes was employed for DSPVs. Panchromatic absorption in the visible region was achieved by mixing N719 and N749 dyes. Ruthenium-based dyes exhibited satisfactory spectral responses to the indoor light sources. The cosensitized DSPV exhibited an excellent efficiency of 20.7% under a 500-lx LED illumination. The charge recombination was reduced in the cosensitized DSPV.